Risk of dengue in Central Africa: Vector competence studies with Aedes aegypti and Aedes albopictus (Diptera: Culicidae) populations and dengue 2 virus. - Basile Kamgang; Marie Vazeille; Armel N Tedjou; Theodel A Wilson-Bahun; Aurélie P Yougang; Laurence Mousson; Charles S Wondji; Anna-Bella Failloux (Public Library of Science (PLoS), 2019)
Introduction Dengue is the most important mosquito-borne diseases worldwide but was considered scarce in West-Central Africa. During the last decade, dengue outbreaks have increasingly been reported in urban foci in this region suggesting major epidemiological changes. However, in Central Africa where both vectors, Aedes aegypti and Aedes albopictus are well established, the role of each species in dengue transmission remains poorly investigated. Methodology/principal findings Field-collected strains of Ae. aegypti and Ae. albopictus from different ecological settings in Central Africa were experimentally challenged with dengue 2 virus (DENV-2). Mosquitoes were analysed at 14- and 21-days post-infection. Analysis provide evidence that both Ae. aegypti and Ae. albopictus in Central Africa were able to transmit dengue virus with Ae. aegypti exhibiting a higher transmission rate. Unexpectedly, two Ae. aegypti populations from Bénoué and Maroua, in northern Cameroon, were not able to transmit DENV-2. Conclusions/significance We conclude that both Ae. aegypti and Ae. albopictus are susceptible to DENV-2 and may intervene as active dengue vectors. These findings highlight the urgent need to plan a vector surveillance program and control methods against dengue vectors in Central Africa in order to prevent future outbreaks.